Structured Reporting of Rectal Magnetic Resonance Imaging in Suspected Primary Rectal Cancer: Potential Benefits for Surgical Planning and Interdisciplinary Communication - Nörenberg, Dominik; Sommer, Wieland H; Thasler, Wolfgang; DʼHaese, Jan; Rentsch, Markus; Kolben, Thomas; Schreyer, Andreas; Rist, Carsten; Reiser, Maximilian; Armbruster, Marco (Investigative radiology, 2017)
The aim of this study was to evaluate the effect of structured reports (SRs) in comparison to nonstructured, free-text (FT) rectal magnetic resonance imaging (MRI) reports in patients with histologically proven rectal cancer and potential effects of both types of reporting on referring surgeons' satisfaction, interdisciplinary communication, and further clinical decision making. The institutional review board approved this retrospective study with waiver of informed consent. Forty-nine patients with histologically proven rectal cancer were included in this study. All patients underwent rectal MRI for local rectal cancer staging before surgery. Free-text reports and SRs for local MR staging of rectal cancer were generated for all subjects by radiologists. Two experienced abdominal surgeons evaluated a questionnaire that included 9 questions regarding satisfaction with content, presence of reported key features, effort for information extraction, and report quality. Structured reports achieved significantly higher satisfaction rates with report content and clarity, and included significantly more of the 13 predefined key features compared with FT reports (SRs: mean ± SD, 12.2 ± 4.6 [range, 9-13] versus FT reports: mean ± SD, 9.2 ± 10.8 [range, 5-13]) (P < 0.001). Definite further clinical decision making (surgery vs neoadjuvant radiochemotherapy) was possible in 96% of SRs and only in 60% of FT reports (P < 0.001). In case of surgery, the reported information was considered to be sufficient for surgical planning in 94% of SRs versus only 38% in FT reports (P < 0.001). Structured report received a significantly higher overall report quality rated on a Likert scale from 1 to 6 (1, insufficient; 6, excellent) with a mean of 5.8 ± 0.42 (range, 5-6) in comparison to FT reports with 3.6 ± 1.19 (range, 1-5) (P < 0.001). Structured reporting of rectal MRI in patients with rectal cancer facilitates surgical planning and leads to a higher satisfaction level of referring surgeons in comparison to FT reports. Abdominal surgeons were more confident about report correctness and further clinical decision making on the basis of SRs.